ANALISA CAMPURAN MINYAK PLASTIK DENGAN PERTAMAX TERHADAP PERFORMA DAN EMISI GAS BUANG HONDA BEAT 2011 - Faat Nur Rhomadhon; Wawan Trisnadi Putra; Fadelan Fadelan (KOMPUTEK, 2022)
Plastic oil is the result of the conversion of plastic waste into fuel oil. The use of plastic waste oil is not directly at 100% use, but it is necessary to have the right dose so that it can be used as a mixture. The method used in this study is experimental research, namely several variations that are carried out successively to the same subject and determine the performance and exhaust emissions on a motorcycle with a mixture of Pertamax and plastic oil and has a CP10 code (pertamax 90% + plastic oil). 10%), CP20 (pertamax 80% + plastic oil 20%), and CP30 (firstmax 70% + plastic oil 30%). The results of all tests of the highest torque occurred in the CP30 mixture of 14,593 Nm at 3000 rpm and the highest power results in the CP30 mixture of 7.1 Kw at 5000 rpm. In the test results the best CO exhaust emissions occurred in the CP10 mixture with emission levels of 1.69% at 5500 rpm while the best HC exhaust emission test results are in the CP10 mixture, which is 81 ppm at 5500 rpm. The lower the CO and HC exhaust gas emission levels, the more efficient the fuel and the more complete combustion.